العلاقة بين تدريب إلقاء المحاضرة بالعربية ومهارة كتابة الإنشاء للصف الثاني في المرحلة الثانوية بمعهد التربية الإسلامية الحديثة الحسنى باجان باتو رياو - Hazimah, Hazimah; Manik, Wagiman; ulum, bahrul (Cahaya Ilmu Bangsa Institute, 2025)
ABSTACT The formulations of the problems in this study are how are the students' abilities in developing their skills in writing insya' both about religion and the world, how is the level of interest of students and teachers in developing the skills of writing insya', to what extent are teachers' abilities in using facilities in learning insya', and is there a relationship between muhadharah extracurricular and the ability to write insya' in class II Aliyah students of the Al-Husna Modern Islamic Boarding School Bagan Batu, Riau? The specific objective of this study was to determine the relationship between muhadharah extracurricular and the ability to write insya' in class II Aliyah students of the Al-Husna Modern Islamic Boarding School Bagan Batu, Riau. And the result is that there is a relationship between muhadharah extracurricular and the ability to write insya' in class II Aliyah students of the Al-Husna Modern Islamic Boarding School Bagan Batu Riau with a value of 0.652 which indicates that the relationship is normal but not unidirectional. So the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The conclusion is that there is a normal relationship between extracurricular muhadharah and writing ability insha'. تجريد أسئلة البحث كيف كانت قدرة الطالبات في تطوير إنشاء المعلومات الدينية والدنيوية من جهة كتابة الإنشاء، وكيف كانت الرغبة في تدريب كتابة الإنشاء من جهة الطالبات والمدرس، وكيف كانت مهارة المدرس عند استخدام الوسيلة التعليمية في تطوير دراسة الإنشاء، وهل هناك العلاقة بين تدريب إلقاء المحاضرة بالعربية ومهارة كتابة الإنشاء؟ و هدفه الخاص لمعرفة العلاقة بين تدريب إلقاء المحاضرة بالعربية ومهارة كتابة الإنشاء لدى الطالبات للصف الثاني في المرحلة الثانوية بمعهد التربية الإسلامية الحديثة الحسنى باجان باتو رياو. والمنهج المستخدم هو المنهج الكمي بالنوع العلاقي وطريقة تحليل البيانات المستعملة هي طريقة إحصائية بالرمز علاقة ضرب العزم (Product Moment) ونتيجة البحث هناك العلاقة بين تدريب إلقاء المحاضرة بالعربية ومهارة كتابة الإنشاء لدى الطالبات للصف الثاني في المرحلة الثانوية بمعهد التربية الإسلامية الحديثة الحسنى باجان باتو رياو بقيمة معامل الارتباط 0،652، والعلاقة معتدلة وليست بنفس الاتجاه. فالفريضة التبادلية (Ha) مقبولة والفريضة العدمية (Ho) مردودة. والخلاصة وجود العلاقة بنهما والعلاقة معتدلة.